2018
DOI: 10.1088/1361-6528/aad75f
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical self-assembly flower-like ammonium nickel phosphate as high-rate performance electrode material for asymmetric supercapacitors with enhanced energy density

Abstract: Ammonium nickel phosphate has a large specific capacitance as an electrode material at low current density, but its capacitance decays fast at high current density, which directly affects the rate performance of supercapacitors. Herein, we demonstrate a facile route for the controllable synthesis of hierarchical self-assembly flower-like ammonium nickel phosphate as a high-rate electrode material for asymmetric supercapacitors, which is an important strategy to enhance the energy density at high power density.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…54−56 The excellent specific energy might result from the high SC as well as the large voltage window (2 V), which were the crucial factors to improve the specific energy because of the following formula: E = 0.5 CV 2 . 1,57 The cycle lifespan of the device in neutral Na 2 SO 4 electrolytes at 1 A g −1 showed that S-3//C, S-4//C and S-5//C could keep about 94%, 93% and 90% SC after a 5000 cycle test, demonstrating the outstanding stability of the devices (Figure 5e). Figure 5f shows that the impedance of S-3//C was lower than S-4//C and S-5//C devices, indicating the outstanding electric conductivity of S-3//C asymmetric supercapacitors.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…54−56 The excellent specific energy might result from the high SC as well as the large voltage window (2 V), which were the crucial factors to improve the specific energy because of the following formula: E = 0.5 CV 2 . 1,57 The cycle lifespan of the device in neutral Na 2 SO 4 electrolytes at 1 A g −1 showed that S-3//C, S-4//C and S-5//C could keep about 94%, 93% and 90% SC after a 5000 cycle test, demonstrating the outstanding stability of the devices (Figure 5e). Figure 5f shows that the impedance of S-3//C was lower than S-4//C and S-5//C devices, indicating the outstanding electric conductivity of S-3//C asymmetric supercapacitors.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The PVA-KOH gel electrolytes were fabricated following a previous report. 57 The mass balancing of the electrode materials would be obey the relationship q + = q − . 58…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As shown in Figure f, there are two large arcs in the Nyquist plots for the 3D porous RHs–Si/C nanocomposite before cycling. The high‐frequency arc presented the sum of contact resistance and resistance of the SEI film formed from electrolyte decomposition . The middle and low‐frequency arcs presented the charge transfer resistance.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Since no one, has ever attempted on finding optimal graphene quantum dots (GQD) mass concentration dispersoid for manganese ammonium phosphate (MnAP) host, the present investigation is ventured on it, and enhancing its specific capacitance by using dual redox additives KI/VOSO 4 has also been investigated for the first time toward high-performance SUPAT application. 29…”
Section: Introductionmentioning
confidence: 99%